High-strength hydrogel with high Tlum and delta Tsol and adjustable tau c as well as preparation method and application of high-strength hydrogel
Through the high-intensity hydrogel copolymerized with hydrophobic polyether side chains and hydrophilic monomers, the existing thermochromic hydrogels have been solved, and the problem of insufficient intensity, light transmittance and modulation ability of existing thermochromic hydrogels has been achieved, and high light transmittance is achieved and modulation capability, and adjust phase change temperature through hydration temperature, suitable for efficient applications of smart windows.
Patent Information
- Application Number
- CN202411444127.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing thermochromic hydrogels perform poorly in intensity, light transmittance (Tlum) and solar modulation capability (ΔTsol), and phase transition temperature (τc) cannot be adjusted, limiting the application of smart windows and large-scale production. .
The hydrophobic polyether side chain monomer is used to copolymerize with the hydrophilic monomer to form a high-strength hydrogel that can self-assemble into micelles before phase transition, and the strength of the hydrogel is increased through hydrophobic association and hydrogen bond crosslinking. , and adjust the phase change temperature through hydration temperature to achieve high light transmittance and high solar light modulation capabilities.
Achieve high light transmittance (Tlum) and high solar modulation capability (ΔTsol), and adjust the phase transition temperature without changing the components through physical crosslinking, improving the mechanical properties and thermal discoloration capability of the hydrogel. .
Smart Images

Figure CN119192466A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogel materials, and in particular to a high-strength hydrogel with high Tlum, ΔTsol and adjustable τc, and a preparation method and application thereof. Background Art
[0002] Building energy costs account for approximately 40% of total global energy consumption. Windows are one of the least efficient components, accounting for 60% of building energy consumption. In terms of total global primary energy use, window-related heating and cooling energy consumption in buildings accounts for approximately 4%. In order to achieve optimal energy savings, smart windows have been developed that can switch between different optical states, which are triggered by thermal, mechanical, electrical or light stimuli. Among these strategies, thermochromic windows are the most direct and environmentally friendly because they can autonomously adjust the transmittance through heating by solar radiation without the need for additional equipment or energy input.
[0003] Previous studies have mainly focused on vanadium dioxide (VO2), which can undergo a metal-insulator transition at a critical transition temperature (τc) of 68°C, leading to a huge transmittance contrast in the infrared (IR) range; however, the intrinsic yellow-brown color and high τc of VO2 result in low light transmittance (Tlum) (<40%) and solar light modulation ability (ΔTsol) (<20%), which limits practical applications.
[0004] Thermochromic hydrogels are ideal materials for smart windows due to their low LCST, high Tlum, and convenience. When the temperature is below τc, the hydrogel is uniform and highly transparent; when the temperature is above τc, the polymer chains aggregate, the hydrogel undergoes a phase transition, and eventually becomes inhomogeneous and opaque. However, due to weak intermolecular forces, PNIPAM-based hydrogels have weak mechanical properties (tensile strength <100 kPa). At the same time, in order to prevent the aggregation of polymer chains and the reduction of Tlum during the polymerization process, the preparation process of the hydrogel often needs to be carried out at low temperatures, which limits the large-scale production of smart windows.
[0005] The chemical crosslinkers of hydrogels restrict the movement of polymer chains, thereby reducing the transition rate between opaque and transparent states. Although some physically crosslinked supramolecular hydrogels with fast transition rates have been reported recently, their mechanical properties and ΔTsol are not satisfactory. Traditional hydrogel smart windows with fixed τc cannot meet the needs of seasonal changes and personalized customization. Although some studies claim that hydrogel smart windows have adjustable τc, the adjustability usually depends on the change of material composition, which may cause the hydrogel properties (such as strength, ΔTsol and Tlum) to be impaired.
[0006] Therefore, it is necessary to develop a better high-strength hydrogel with high Tlum, ΔTsol and adjustable τc. Summary of the invention
[0007] The purpose of the present invention is to provide a high-strength hydrogel with high Tlum, ΔTsol and adjustable τc, and its preparation method and application. The present invention provides a high-strength hydrogel with high Tlum (light transmittance), ΔTsol (sunlight modulation ability) and adjustable τc (phase transition temperature) under the same component. The hydrogel is obtained by copolymerizing a hydrophobic monomer containing a polyether structure in the side chain with a hydrophilic monomer. The hydrophobic polyethylene glycol side groups in the hydrogel self-assemble to form micelles. The thermochromic hydrogel of the present invention is uniform and highly transparent before the phase change, with high light transmittance. When the temperature exceeds τc, phase separation occurs to form a polymer-rich phase and a water-rich phase. Light is scattered between the two phases. After the phase change, the light transmittance of the hydrogel is greatly reduced, thereby having excellent thermochromic ability and effectively improving ΔTsol.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] The first aspect of the present invention is to provide a high-strength hydrogel with high Tlum, ΔTsol and adjustable τc, which is obtained by copolymerizing raw materials including hydrophobic monomers and hydrophilic monomers;
[0010] The hydrophobic monomer is a hydrophobic monomer containing a polyether structure;
[0011] The hydrophilic monomer is a monomer containing at least one hydrophilic group selected from the group consisting of a carboxyl group, a hydroxyl group, and an amino group.
[0012] As a preferred embodiment,
[0013] The hydrophobic monomer is a monomer having a polyether segment in the side chain; and / or,
[0014] The hydrophilic monomer is one or more of acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxyethyl methacrylate or acrylamide; and / or,
[0015] The raw materials of the hydrogel also include a photoinitiator.
[0016] As a preferred embodiment,
[0017] Based on the total mass of the hydrophobic monomer and the hydrophilic monomer as 100%, the hydrophobic monomer accounts for 90wt%-40wt%; and / or,
[0018] For every 10 ml of the mixture of the hydrophobic monomer and the hydrophilic monomer, 20-50 μL of a photoinitiator is added, wherein the photoinitiator accounts for 0.2%-0.5% of the total mass of the hydrophobic monomer and the hydrophilic monomer; and / or,
[0019] The general structural formula of the hydrophobic monomer is shown in Formula 1:
[0020]
[0021] Wherein, the value range of n is 2-20; R1 is a C1-C2 alkyl group; and R2 is a H atom or a methyl group.
[0022] As a preferred embodiment,
[0023] Taking the total mass of the hydrophobic monomer and the hydrophilic monomer as 100%, the proportion of the hydrophobic monomer is 80wt%-60wt%;
[0024] The hydrophobic monomer is at least one of 2-(2-ethoxyethoxy)ethyl acrylate (EEEA) or 2-[2-(2-methoxyethoxy)ethoxy]ethyl acrylate (MEEEA); and / or,
[0025] The photoinitiator is at least one of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-hydroxy-2-methyl-1-phenyl-1-propanone or 1-hydroxycyclohexyl phenyl ketone.
[0026] As a preferred embodiment,
[0027] The high-strength hydrogel has different critical transition temperatures (phase transition temperatures) τc at the same component ratio based on different hydration temperatures during preparation; preferably, the τc (critical transition temperature) of the high-strength hydrogel is 4-70°C, more preferably 25-50°C; and / or,
[0028] The Tlum (light transmittance) of the high-strength hydrogel is 98%-80%, preferably 85%-95%; and / or,
[0029] The ΔTsol (solar light modulation capability) of the high-strength hydrogel is 50%-88%, preferably 60%-85%; and more preferably 70%-85%.
[0030] As a preferred embodiment,
[0031] The elongation at break of the high-strength hydrogel is 190-500%, preferably 300-400%; and / or,
[0032] The tensile strength of the high-strength hydrogel is 150-500 kPa, preferably 250-450 kPa; and / or,
[0033] The modulus of the high-strength hydrogel is 140-300 kPa, preferably 170-250 kPa.
[0034] The second aspect of the present invention is to provide a method for preparing a high-strength hydrogel having high Tlum, ΔTsol and adjustable τc as described in the first aspect of the present invention, comprising the following steps:
[0035] Step (1): subjecting a hydrophobic monomer, a hydrophilic monomer and a photoinitiator to a bulk polymerization reaction under ultraviolet light to obtain an elastomer;
[0036] Step (2): hydrating the elastomer to form the high-strength hydrogel having high Tlum, ΔTsol and adjustable τc.
[0037] As a preferred embodiment,
[0038] In step (1), the light intensity under the ultraviolet light is 2-20 mW / cm 2 and / or,
[0039] The wavelength of the ultraviolet light is 254nm-405nm; and / or,
[0040] The polymerization reaction time is 0.5-4 hours; and / or,
[0041] In step (2), the hydration method is to immerse the elastomer in ultrapure water and change the ultrapure water regularly.
[0042] As a preferred embodiment,
[0043] In step (1), the light intensity under the ultraviolet light is 5-10mW / cm 2 and / or,
[0044] The wavelength of the ultraviolet light is 254nm, 365nm, 405nm; and / or,
[0045] The polymerization reaction time is 2-3 hours.
[0046] The third aspect of the present invention is to provide a high-strength hydrogel with high Tlum, ΔTsol and adjustable τc as described in the first aspect of the present invention for use in the field of thermochromic windows.
[0047] Beneficial effects brought by the technical solution of the present invention
[0048] The present invention aims at the problem that the thermochromic hydrogel in the prior art has low strength, Tlum and ΔTsol, and τc cannot be adjusted. The present invention selects monomers with hydrophobic polyether side chains to copolymerize with hydrophilic monomers. The hydrophobic monomers can self-assemble into micelles and can undergo phase separation above τc, thereby greatly reducing the solar transmittance, thereby giving the hydrogel a high ΔTsol.
[0049] The hydrophobic association between the hydrophobic polyether side chains and the hydrogen bond cross-linking between the hydrophilic monomers endow the hydrogel with high strength.
[0050] The hydrogel of the present invention is completely physically cross-linked, and its τc is determined by the hydration temperature during preparation. When immersed in water at different temperatures for a long time, the hydrogel can absorb / expel water in the micelles and rearrange the molecular chains, thereby achieving τc regulation without changing the components. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 is the hydrogel reaction equation of Example 1 of the present invention;
[0052] Figure 2 This is the infrared spectrum of the hydrogel of Example 1 of the present invention;
[0053] Figure 3 This is a test diagram of the mechanical properties of the hydrogel of Example 1 of the present invention;
[0054] Figure 4 This is a test diagram of the optical properties of the hydrogel of Example 1 of the present invention;
[0055] Figure 5 This is a test diagram of the mechanical properties of the hydrogel of Example 2 of the present invention;
[0056] Figure 6 This is a test diagram of the optical properties of the hydrogel of Example 2 of the present invention;
[0057] Figure 7 This is a test diagram of the mechanical properties of the hydrogel of Example 3 of the present invention;
[0058] Figure 8 This is a test diagram of the optical properties of the hydrogel of Example 3 of the present invention;
[0059] Fig. 9 This is a test diagram of the mechanical properties of the hydrogel of Example 4 of the present invention;
[0060] Fig.10 This is a test diagram of the optical properties of the hydrogel of Example 4 of the present invention;
[0061] Fig.11 This is a test diagram of the mechanical properties of the hydrogel of Example 5 of the present invention;
[0062] Fig.12 This is a test diagram of the optical properties of the hydrogel of Example 5 of the present invention;
[0063] Fig.13 This is a test diagram of the mechanical properties of the hydrogel of Comparative Example 1 of the present invention;
[0064] Fig.14This is a test diagram of the optical properties of the hydrogel in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0065] The present invention is further described in detail below through the accompanying drawings and specific embodiments.
[0066] Example 1
[0067] (1) Based on the total mass of the hydrophobic monomer and the hydrophilic monomer as 100%, 80 wt% of 2-(2-ethoxyethoxy)ethyl 2-acrylate (EEEA) and 20 wt% of acrylic acid (AAc) were stirred on a magnetic stirrer for 8 minutes to obtain a uniformly mixed solution.
[0068] (2) Add the photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone to the solution obtained in step (1) (30 μL of photoinitiator per 10 ml of solution) and stir for 10 minutes to obtain a uniform solution.
[0069] (3) The solution obtained in step (2) was injected into the middle of two glass plates separated by a silicone gasket (thickness 1 mm), and then the glass plates were placed in a UV cross-linking instrument under a wavelength of 254 nm and a light intensity of 10 mW / cm 2 The EA elastomer was obtained by polymerization for 2 hours.
[0070] (4) The PEA elastomer obtained in step (3) is immersed in ultrapure water at 25°C for 72 hours, and the ultrapure water is replaced every 12 hours. The elastomer is hydrated to form a hydrogel and the unpolymerized monomer is discharged, and finally a PEA hydrogel is obtained. The reaction equation of PEA hydrogel is as follows: Figure 1 shown.
[0071] like Figure 2 As shown in the figure, the PEA hydrogel structure was characterized by attenuated total reflectance infrared spectroscopy (ATR-FTIR), where the wave number was 1728 cm -1 The peak at 1250-1100cm is the characteristic peak of carboxyl group. -1 The three peaks at correspond to the characteristic peaks of three CO in the polyethylene glycol side group in the hydrophobic monomer, respectively. The above results prove that 2-acrylate-2-(2-ethoxyethoxy)ethyl ester (EEEA) and acrylic acid (AAc) in the present invention are successfully polymerized.
[0072] like Figure 3 As shown, the dumbbell-shaped hydrogel was subjected to a tensile test by a universal testing machine to characterize its mechanical properties. The tensile strength of the hydrogel was 380 kPa, the elongation at break was 377%, and the modulus was 170 kPa.
[0073] like Figure 4As shown, the optical properties of the hydrogel were measured by UV-visible-near infrared spectrophotometer in the wavelength range of 300-2500nm. Before the phase change, the PEA hydrogel of the present invention had a high sunlight transmittance (>80%). Before and after τc, the visible light transmittance of the hydrogel decreased from 92.69% to 1.813%, proving that the hydrogel has excellent thermochromic ability.
[0074] Example 2
[0075] (1) 70 wt % of 2-(2-ethoxyethoxy)ethyl 2-acrylate (EEEA) and 30 wt % of acrylic acid (AAc) were stirred on a magnetic stirrer for 8 minutes to obtain a uniformly mixed solution.
[0076] (2) Add the photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone to the solution obtained in step (1) (30 μL of photoinitiator per 10 ml of solution) and stir for 10 minutes to obtain a uniform solution.
[0077] (3) The solution obtained in step (2) was injected into the middle of two glass plates separated by a silicone gasket (thickness 1 mm), and then the glass plates were placed in a UV cross-linking instrument under a wavelength of 254 nm and a light intensity of 10 mW / cm 2 The PEA elastomer was obtained by polymerization for 2 hours.
[0078] (4) Soaking the PEA elastomer obtained in step (3) in ultrapure water at 25° C. for 72 hours, replacing the ultrapure water every 12 hours, so that the elastomer is hydrated to form a hydrogel and unpolymerized monomers are discharged, thereby finally obtaining a PEA hydrogel.
[0079] like Figure 5 As shown, the dumbbell-shaped hydrogel was subjected to a tensile test by a universal testing machine to characterize its mechanical properties. The tensile strength of the hydrogel was 430 kPa, the elongation at break was 465%, and the modulus was 210 kPa.
[0080] like Figure 6 As shown, the optical properties of the hydrogel were measured by UV-visible-near infrared spectrophotometer in the wavelength range of 300-2500nm. Before the phase change, the PEA hydrogel of the present invention had a high sunlight transmittance (>80%). Before and after τc, the visible light transmittance of the hydrogel decreased from 92.23% to 10.15%, proving that the hydrogel has excellent thermochromic ability.
[0081] Example 3
[0082] (1) 80 wt% of 2-(2-ethoxyethoxy)ethyl 2-acrylate (EEEA) and 20 wt% of hydroxyethyl acrylate (HEA) were stirred on a magnetic stirrer for 10 minutes to obtain a uniform solution.
[0083] (2) Add the photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone to the solution obtained in step (1) (30 μL of photoinitiator per 10 ml of solution) and stir for 10 minutes to obtain a uniform solution.
[0084] (3) The solution obtained in step (2) was injected into the middle of two glass plates separated by a silicone gasket (thickness 1 mm), and then the glass plates were placed in a UV cross-linking instrument under a wavelength of 254 nm and a light intensity of 10 mW / cm 2 The PEH elastomer was obtained by polymerization for 2 hours.
[0085] (4) Soaking the PEH elastomer obtained in step (3) in ultrapure water at 25° C. for 72 hours, replacing the ultrapure water every 12 hours, so that the elastomer is hydrated to form a hydrogel and unpolymerized monomers are discharged, thereby finally obtaining a PEH hydrogel.
[0086] like Figure 7 As shown, the dumbbell-shaped hydrogel was subjected to a tensile test by a universal testing machine to characterize its mechanical properties. The tensile strength of the hydrogel was 165 kPa, the elongation at break was 190%, and the modulus was 160 kPa.
[0087] like Figure 8 As shown, the optical properties of the hydrogel were measured by UV-visible-near infrared spectrophotometer in the wavelength range of 300-2500nm. Before the phase change, the PEH hydrogel of the present invention had a high sunlight transmittance (>80%). Before and after τc, the visible light transmittance of the hydrogel decreased from 86.14% to 27.37%, proving that the hydrogel has excellent thermochromic ability.
[0088] Example 4
[0089] (1) 70 wt % of 2-[2-(2-methoxyethoxy)ethoxy]ethyl acrylate (MEEEA) and 30 wt % of acrylic acid (AAc) were stirred on a magnetic stirrer for 10 minutes to obtain a uniform solution.
[0090] (2) Add the photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone to the solution obtained in step (1) (30 μL of photoinitiator per 10 ml of solution) and stir for 10 minutes to obtain a uniform solution.
[0091] (3) The solution obtained in step (2) was injected into the middle of two glass plates separated by a silicone gasket (thickness 1 mm), and then the glass plates were placed in a UV cross-linking instrument under a wavelength of 254 nm and a light intensity of 10 mW / cm 2 The PMEH elastomer was obtained by polymerization at 400 °C for 2 hours.
[0092] (4) The PMEH elastomer obtained in step (3) is immersed in ultrapure water at 25° C. for 72 hours, and the ultrapure water is replaced every 12 hours. The elastomer is hydrated to form a hydrogel and unpolymerized monomers are discharged, thereby finally obtaining a PMEH hydrogel.
[0093] like Fig. 9 As shown, the dumbbell-shaped hydrogel was subjected to a tensile test by a universal testing machine to characterize its mechanical properties. The tensile strength of the hydrogel was 280 kPa, the elongation at break was 680%, and the modulus was 146 kPa.
[0094] like Fig.10 As shown, the optical properties of the hydrogel were measured by UV-Vis-NIR spectrophotometer in the wavelength range of 300-2500nm. Before the phase change, the PMEA hydrogel of the present invention had a high sunlight transmittance (>80%). Before and after τc, the visible light transmittance of the hydrogel decreased from 88.35% to 3.225%, proving that the hydrogel has excellent thermochromic ability.
[0095] Example 5
[0096] (1) Based on the total mass of the hydrophobic monomer and the hydrophilic monomer as 100%, 80 wt% of 2-(2-ethoxyethoxy)ethyl 2-acrylate (EEEA) and 20 wt% of acrylic acid (AAc) were stirred on a magnetic stirrer for 8 minutes to obtain a uniformly mixed solution.
[0097] (2) Add the photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone to the solution obtained in step (1) (30 μL of photoinitiator per 10 ml of solution) and stir for 10 minutes to obtain a uniform solution.
[0098] (3) The solution obtained in step (2) was injected into the middle of two glass plates separated by a silicone gasket (thickness 1 mm), and then the glass plates were placed in a UV cross-linking instrument under a wavelength of 254 nm and a light intensity of 10 mW / cm 2 The EA elastomer was obtained by polymerization for 2 hours.
[0099] (4) The PEA elastomer obtained in step (3) is immersed in ultrapure water at 50° C. for 72 hours, and the ultrapure water is replaced every 12 hours. The elastomer is hydrated to form a hydrogel and unpolymerized monomers are discharged, thereby finally obtaining a PEA hydrogel.
[0100] like Fig.11 As shown, the dumbbell-shaped hydrogel was subjected to a tensile test by a universal testing machine to characterize its mechanical properties. The tensile strength of the hydrogel was 224 kPa, the elongation at break was 220%, and the modulus was 208 kPa.
[0101] like Fig.12 As shown, the optical properties of the hydrogel were measured by UV-Vis-NIR spectrophotometer in the wavelength range of 300-2500nm. At 25 and 50°C, the hydrogel maintained a high visible light transmittance (89.51% and 89.28%, respectively). When the temperature exceeded τc, the visible light transmittance of the hydrogel decreased to 4.955%.
[0102] Comparative Example 1
[0103] (1) 2 g of N-isopropylacrylamide, 12 mg of N,N'-methylenebisacrylamide and 40 μL of tetramethylethylenediamine were magnetically dissolved in 10 ml of water and stirred on a stirrer for 8 minutes to obtain a uniform solution.
[0104] (2) To the solution obtained in step (1), add 6 mg of thermal initiator ammonium persulfate and stir for 10 minutes to obtain a uniform solution.
[0105] (3) The solution obtained in step (2) was injected into the middle of two glass plates separated by a silicone gasket (thickness 1 mm), and then the glass plates were placed in a refrigerator at 4°C for thermal polymerization to form a PNIPAM hydrogel.
[0106] like Fig.13 As shown, the dumbbell-shaped hydrogel was subjected to a tensile test by a universal testing machine to characterize its mechanical properties. The tensile strength of the hydrogel was 4 kPa, the elongation at break was 1.2%, and the modulus was 5 kPa.
[0107] like Fig.14 As shown, the optical properties of the hydrogel were measured by UV-visible-near infrared spectrophotometer in the wavelength range of 300-2500 nm. The visible light transmittance of the hydrogel decreased from 82.3% to 16.66% before and after τc.
[0108] The test data of Tlum, ΔTsol, τc and strength of the above embodiments and comparative examples are summarized in Table 1.
[0109] Table 1
[0110]
[0111]
[0112] It can be seen from the results of the above embodiments that the thermochromic hydrogel of the present invention does not need to be prepared at low temperature, and the prepared thermochromic hydrogel has high elongation at break, tensile strength and modulus, that is, the thermochromic hydrogel of the present invention has high strength and has very good application value.
[0113] From the results of the above embodiments, it can be seen that the thermochromic hydrogel of the present invention is uniform and highly transparent before phase change, with high light transmittance. When the temperature exceeds τc, phase separation occurs to form a polymer-rich phase and a water-rich phase. Light is scattered between the two phases, and the light transmittance of the hydrogel is greatly reduced, so that it has excellent thermochromic ability, thereby effectively improving the sunlight modulation ability ΔTsol.
[0114] From the comparison of the results of Example 1 and the comparative example, it can be seen that the thermochromic hydrogel of the present invention has better strength, light transmittance and sunlight modulation ability than the existing thermochromic hydrogel.
[0115] From Example 5 Fig.12 The results show that the high-strength hydrogel has different critical transition temperatures (phase transition temperatures) at the same component ratio based on different hydration temperatures during preparation. This is because the hydrophobic association between the hydrophobic polyether side chains and the hydrogen bond crosslinking between the hydrophilic monomers give the hydrogel high strength. Since the hydrogel is completely physically crosslinked, its τc is determined by the hydration temperature during preparation. When immersed in water at different temperatures for a long time, the hydrogel can absorb / expel water in the micelles and rearrange the molecular chains, thereby achieving τc adjustment without changing the components.
[0116] The above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A high-strength hydrogel with high Tlum, ΔTsol and adjustable τc, characterized in that: Obtained by copolymerization of raw materials including hydrophobic monomers and hydrophilic monomers; The hydrophobic monomer is a hydrophobic monomer containing a polyether structure; The hydrophilic monomer is a monomer containing at least one hydrophilic group selected from the group consisting of a carboxyl group, a hydroxyl group, and an amino group.
2. The high-strength hydrogel with high Tlum, ΔTsol and adjustable τc according to claim 1, characterized in that: The hydrophobic monomer is a monomer having a polyether segment in the side chain; and / or, The hydrophilic monomer is one or more of acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxyethyl methacrylate or acrylamide; and / or, The raw materials of the hydrogel also include a photoinitiator.
3. The high-strength hydrogel with high Tlum, ΔTsol and adjustable τc according to claim 2, characterized in that: Based on the total mass of the hydrophobic monomer and the hydrophilic monomer as 100%, the hydrophobic monomer accounts for 90wt%-40wt%; and / or, To every 10 ml of the mixture of hydrophobic monomer and hydrophilic monomer, add 20-50 μL of photoinitiator; and / or, The general structural formula of the hydrophobic monomer is shown in Formula 1: Wherein, the value range of n is 2-20; R1 is a C1-C2 alkyl group; and R2 is a H atom or a methyl group.
4. The high-strength hydrogel with high Tlum, ΔTsol and adjustable τc according to claim 2, characterized in that: Taking the total mass of the hydrophobic monomer and the hydrophilic monomer as 100%, the proportion of the hydrophobic monomer is 80wt%-60wt%; The hydrophobic monomer is at least one of 2-(2-ethoxyethoxy)ethyl acrylate and 2-[2-(2-methoxyethoxy)ethoxy]ethyl acrylate; and / or, The photoinitiator is at least one of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-hydroxy-2-methyl-1-phenyl-1-propanone or 1-hydroxycyclohexyl phenyl ketone.
5. The high-strength hydrogel with high Tlum, ΔTsol and adjustable τc according to claim 1, characterized in that: The high-strength hydrogel has different critical transition temperatures τc at the same composition ratio based on different hydration temperatures during preparation; preferably, the τc of the high-strength hydrogel is 4-70°C, more preferably 25-50°C; and / or, The light transmittance Tlum of the high-strength hydrogel is 98%-80%, preferably 85%-95%; and / or, The solar light modulation capacity ΔTsol of the high-strength hydrogel is 50%-88%, preferably 60%-85%; and more preferably 70%-85%.
6. The high-strength hydrogel with high Tlum, ΔTsol and adjustable τc according to claim 1, characterized in that: The elongation at break of the high-strength hydrogel is 190-500%, preferably 300-400%; and / or, The tensile strength of the high-strength hydrogel is 150-500 kPa, preferably 250-450 kPa; and / or, The modulus of the high-strength hydrogel is 140-300 kPa, preferably 170-250 kPa.
7. A method for preparing a high-strength hydrogel with high Tlum, ΔTsol and adjustable τc according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step (1): subjecting a hydrophobic monomer, a hydrophilic monomer and a photoinitiator to a bulk polymerization reaction under ultraviolet light to obtain an elastomer; Step (2): hydrating the elastomer to form the high-strength hydrogel having high Tlum, ΔTsol and adjustable τc.
8. The preparation method according to claim 7, characterized in that: In step (1), the light intensity under the ultraviolet light is 2-20 mW / cm 2 and / or, The wavelength of the ultraviolet light is 254nm-405nm; and / or, The polymerization reaction time is 0.5-4 hours; and / or, In step (2), the hydration method is to immerse the elastomer in ultrapure water and change the ultrapure water regularly.
9. The preparation method according to claim 8, characterized in that: In step (1), the light intensity under the ultraviolet light is 5-10mW / cm 2 and / or, The wavelength of the ultraviolet light is 254nm, 365nm, 405nm; and / or, The polymerization reaction time is 2-3 hours.
10. Use of the high-strength hydrogel with high Tlum, ΔTsol and adjustable τc as claimed in any one of claims 1 to 6 in the field of thermochromic windows.
Citation Information
Patent Citations
Smart window capable of switching light transmission state
CN109267906A
Photo-thermal dual-response intelligent window and preparation method thereof
CN115503307A
Preparation method of metal ion in-situ coordination reinforced hydrophilic elastomer as well as product and application of metal ion in-situ coordination reinforced hydrophilic elastomer
CN116589623A
Preparation method of photo-crosslinking intelligent hydrogel and application of photo-crosslinking intelligent hydrogel in dimming glass
CN118667068A
Thermochromic composite material, its preparation and use
US20220242004A1
Cited By
High-rigidity and high-strength phase separation hydrogel and preparation method thereof
CN120192462A
Polymer boron cross-linking agent, ultrahigh-strength hydrogel prepared from polymer boron cross-linking agent and preparation method of ultrahigh-strength hydrogel
CN121895500A
